(untitled) (Indian Journal of Forensic Medicine & Toxicology, 2023)
Sudden unexpected deaths pose a challenge for the forensic pathologists. Usually relates to cardiovascular cause and such deaths due to gastrointestinal related pathology are uncommon. Acute pancreatitis is a major etiology of gastrointestinal sudden deaths. It is mainly associated with gallbladder stones and alcoholism. We report a case of a 48-year-old man, chronic alcoholic, who was brought dead to hospital after complaints of abdominal pain and vomiting. The postmortem examination revealed the death due to acute hemorrhagic pancreatitis. Literature shows pancreatitis to be significantly associated with alcoholic liver disease. The present case reemphasizes the importance of examination of retroperitoneal space during autopsy and how ancillary investigations such as histopathology, chemical analysis, measuring serum amylase, lipase and vitreous glucose levels help in arriving at final diagnosis.